Prostorska razširjenost, habitatne značilnosti in upravljanje s populacijo gamsa (Rupicapra rupicapra L.) na območju Zahodnih Karavank - Černe, Blaž (Gozdarski vestnik, 2012)
Population management of chamois in the western part of the Karavanke range has been a challenge to scientists for decades. The challenge is compounded bythe reluctance of hunters to accept and adopt the recent findings in the field of species ecology, habitat characteristics and influence of environmental factors on spatial distribution, population dynamics, and population density of the species. An area in the Western Karavanke, measuringa total of 40 km in length and covering a surface of approximately 19,000 ha, was studied in the period of August to October to determine the environmental factors having a characteristic impact on the spatial distribution of chamois. Statistical analyses have shown that the occurrence of chamois depends on the values of seven environmental factors. Probability of species occurrence increases with altitude, higher share of rocky areas, higher ratio of forest land to other land uses, and with a higher percentage of built-up and related land. On the other hand, chamois occurrence correlatesnegatively with the increase in the share of pole stand with growing distance from hunting treestands and blinds, and is sensitive to various grazing regimes and patterns.
Keywords: gamsi; Rupicapra rupicapra; habitat; Karavanke; Karawanks